Development of Augmented Reality (AR) Learning Application Integrated with Bima’s Local Culture to Enhance Students' Critical Thinking Skills - Muhammad Salahuddin; Nursidrati; Nur Islamiati; Lisda Ramdhani (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This research aims to develop an Augmented Reality (AR) learning application integrated with Bima's local culture to enhance students' critical thinking skills in geometry lessons at SMPN 3 Woha. The main issues addressed include low digital literacy among teachers and students, as well as limited exposure to local cultural elements—such as uma lengge, sigi raja pertama, uma panggung, and asi mbojo—in mathematics education.The study tackles challenges like inadequate digital skills and the need to preserve Bima's cultural heritage through relevant educational content. The research employed a Research and Development (R&D) model using the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). It involved 40 students as subjects, with data collected via Likert-scale questionnaires, observations, interviews, and pre-post critical thinking tests. Data analysis combined qualitative and quantitative (mixed) methods. The AR application was rated highly valid (scores of 4.6-4.7 by experts), practical (scores of 3.9-4.1 from students), and effective, with critical thinking scores improving from 62.5 to 77.5 (a 24% increase). Local culture integration boosted student engagement and conceptual understanding. The AR application integrated with Bima's local culture proved effective as an innovative learning medium, supporting critical thinking development and cultural preservation.